Polystichum gonggashanense (Dryopteridaceae): a new fern from Sichuan, China - He, Hai; Zhang, Li-Bing (Phytotaxa, 2022)
Polystichum gonggashanense (Dryopteridaceae: sect. Hypopeltis) is described and illustrated from Mt. Gongga (Minyar Gonkar), Sichuan, China. It can be distinguished from its most similar species, P. sinense, by the blackish brown petiole scales, the oblong-lanceolate lamina, and narrowly lanceolate rachis scales. The new species is found in four populations each with a few individuals and one of the populations has already disappeared. It is classified as CR (Critically Endangered) category based on the IUCN criteria.